The Challenges of Working in the Heat Whilst Pregnant: Insights From Gambian Women Farmers in the Face of Climate Change - Spencer, Shantelle; Samateh, Tida; Wabnitz, Katharina; Mayhew, Susannah; Allen, Haddijatou; Bonell, Ana (Frontiers in Public Health, 2022)
Background: The expected increase in heat in The Gambia is one of the most significant health threats caused by climate change. However, little is known about the gendered dynamics of exposure and response to heat stress, including women’s perceived health risks, adaptation strategies to heat, and perceptions of climate change. This research project aims to answer the question of whether and how pregnant farmers in The Gambia perceive and act upon occupational heat stress and its health impacts on both themselves and their unborn children, against the backdrop of current and expected climatic changes. Method: In-depth semi-structured interviews were conducted with 12 women who practice subsistence farming and were either pregnant or had delivered within the past month in West Kiang, The Gambia. Participants were selected using purposive sampling. Translated interview transcripts were coded and qualitative thematic content analysis with an intersectional lens was used to arrive at the results. Results: All women who participated in the study experience significant heat stress while working outdoors during pregnancy, with symptoms often including headache, dizziness, nausea, and chills. The most common adaptive techniques included resting in the shade while working, completing their work in multiple shorter time increments, taking medicine to reduce symptoms like headache, using water to cool down, and reducing the amount of area they cultivate. Layered identities, experiences, and household power structures related to age, migration, marital situation, socioeconomic status, and supportive social relationships shaped the extent to which women were able to prevent and reduce the effects of heat exposure during their work whilst pregnant. Women who participated in this study demonstrated high awareness of climate change and offered important insights into potential values, priorities, and mechanisms to enable effective adaptation. Conclusion: Our findings reveal many intersecting social and economic factors that shape the space within which women can make decisions and take adaptive action to reduce the impact of heat during their pregnancy. To improve the health of pregnant working women exposed to heat, these intersectionalities must be considered when supporting women to adapt their working practices and cope with heat stress.